2020
DOI: 10.1038/s41591-020-0790-y
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic base editing of human hematopoietic stem cells

Abstract: Base editing by nucleotide deaminases linked to programmable DNA-binding proteins represents a promising approach to permanently remedy blood disorders, although its application in engrafting hematopoietic stem cells (HSCs) remains unexplored. Here we purified A3A (N57Q)-BE3 protein for ribonucleoprotein (RNP) electroporation of human peripheral blood (PB) mobilized CD34 + hematopoietic stem and progenitor cells (HSPCs). We observed frequent on-target cytosine base

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
167
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(175 citation statements)
references
References 33 publications
5
167
2
1
Order By: Relevance
“…This is true even with very different modalities of Cas9 (mRNA, recombinant protein), guide RNA (synthetic, adeno-associated virus (AAV) expressed), and HDR donor (single-stranded DNA, AAV6) ( Dever et al., 2016 ; DeWitt et al., 2016 ; Genovese et al., 2014b ; Hoban et al., 2015 ; Kim et al., 2014 ; Wang et al., 2015 ). A recent report also found that a specific subtype of base editing by nucleotide deaminases at the BCL11A erythroid enhancer is less efficient in quiescent human HSCs than in non-quiescent progenitor cells ( Zeng et al., 2020 ). Our results indicate that the observed in vivo lack of HDR is not caused by an inability to target immunophenotypic LT-HSCs, nor toxicity caused by the act of performing HDR itself ( Ihry et al., 2018 ), but is instead because the repopulating HSCs are in an inappropriate phase of the cell cycle to perform HDR.…”
Section: Discussionmentioning
confidence: 99%
“…This is true even with very different modalities of Cas9 (mRNA, recombinant protein), guide RNA (synthetic, adeno-associated virus (AAV) expressed), and HDR donor (single-stranded DNA, AAV6) ( Dever et al., 2016 ; DeWitt et al., 2016 ; Genovese et al., 2014b ; Hoban et al., 2015 ; Kim et al., 2014 ; Wang et al., 2015 ). A recent report also found that a specific subtype of base editing by nucleotide deaminases at the BCL11A erythroid enhancer is less efficient in quiescent human HSCs than in non-quiescent progenitor cells ( Zeng et al., 2020 ). Our results indicate that the observed in vivo lack of HDR is not caused by an inability to target immunophenotypic LT-HSCs, nor toxicity caused by the act of performing HDR itself ( Ihry et al., 2018 ), but is instead because the repopulating HSCs are in an inappropriate phase of the cell cycle to perform HDR.…”
Section: Discussionmentioning
confidence: 99%
“…SaKKH-BE3, a BE with SaCas9-KKH locator, was used to treat phenylketonuria in adult mice through the delivery of adeno-associated virus [89]. Recently, A3A (N57Q)-BE3 was used to edit the enhancer region of B cell lymphoma/leukemia 11A (BCL11A) gene and expression of fetal hemoglobin (HbF) was induced successfully, which showed therapeutic benefits for sickle cell disease and β-thalassemia [90]. In addition to animals, Zong et al successfully applied codon-optimized BE3 [plant base editor (PBE)] in plants [61] and later, the same lab also optimized hA3A-BE3 to develop the plant version of A3A-PBE to achieve higher editing efficiencies in plants [64].…”
Section: Applications Of Bes and Pesmentioning
confidence: 99%
“…Base editing approaches by nucleotide deaminases linked to synthesized CRISPR guides to target the erythroid enhancer region of BCL11A are also in early stages of development 57 …”
Section: Methodsmentioning
confidence: 99%